Smartphone-Assisted Thin-Layer Chromatography for Rapid Quality Screening of Metformin - Ram Kumar Bhattarai; Sanam Pudasaini; Toni Barstis; Basant Giri (Advances in Pharmacological and Pharmaceutical Sciences)
Type II diabetes remains a significant global public health issue, affecting both individual well-being and healthcare systems worldwide. Metformin hydrochloride is widely prescribed as the first-line treatment for managing diabetes. However, the increasing reports of substandard and falsified medicines, including metformin, circulating in the markets in recent years, highlights the urgent need for reliable and portable quality assurance tools. Thin-layer chromatography (TLC) has long been extensively used as a screening method to verify the identity and quality of various medicines. In this work, we present a smartphone-assisted TLC method for quantitative analysis of metformin hydrochloride. The TLC was performed using silica gel 60 F254 plates as the stationary phase and acetic acid-methanol-water 0.25:7:4 (v/v) as a mobile phase. We used a custom-made UV-illuminated TLC imaging box to capture images via smartphone and images were analyzed using a custom written smartphone application to calculate the Rf and the concentration of metformin in the principal TLC spots. The smartphone application, TLC Analyzer, accurately calculated the Rf values (0.604) consistent with those obtained using ImageJ software. The linearity of the method was 0.5–4 mg/mL. After optimization, the TLC Analyzer method was used to analyze metformin samples (n = 16) collected from local pharmacies. The results were compared with those from ImageJ analysis, UV–Vis spectrophotometry, and HPLC. The smartphone-based TLC Analyzer method identified 15 of the 16 samples as containing acceptable levels of metformin in accordance with pharmacopeial standards, consistent with ImageJ and spectrophotometric results. In contrast, the HPLC method indicated that all 16 samples met the pharmacopeial criteria.